2022
DOI: 10.1111/bph.15844
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mitochondrial proteases for therapy of acute myeloid leukaemia

Abstract: Targeting cancer metabolism has emerged as an attractive approach to improve therapeutic regimens in acute myeloid leukaemia (AML). Mitochondrial proteases are closely related to cancer metabolism, but their biological functions have not been well characterized in AML. According to different categories, we comprehensively review the role of mitochondrial proteases in AML. This review highlights some ‘powerful’ mitochondrial protease targets, including their biological function, chemical modulators, and applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 156 publications
0
6
0
Order By: Relevance
“…Homo sapiens Casein lysing protease P (HsClpP), located in the mitochondrial matrix, functionally maintains the integrity of OXPHOS. Activation of HsClpP by chemical or genetic strategy leads to impaired OXPHOS and selectively kills AML cells and stem cells in vitro and in vivo , rather than normal hematopoietic cells. , More importantly, mitochondrial HsClpP is overexpressed in 45% of primary AML samples, helping to achieve selective regulation of OXPHOS …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Homo sapiens Casein lysing protease P (HsClpP), located in the mitochondrial matrix, functionally maintains the integrity of OXPHOS. Activation of HsClpP by chemical or genetic strategy leads to impaired OXPHOS and selectively kills AML cells and stem cells in vitro and in vivo , rather than normal hematopoietic cells. , More importantly, mitochondrial HsClpP is overexpressed in 45% of primary AML samples, helping to achieve selective regulation of OXPHOS …”
Section: Introductionmentioning
confidence: 99%
“…Especially in glioma, up to 12 related clinical trials are underway . In AML, relevant clinical studies include NCT02392572 in relapsed/refractory AML or high-risk myelodysplastic syndromes and NCT03932643 (maintenance therapy after stem cell transplant) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AML is the most common form of acute leukemia found in adults ( Greiner, Gotz & Wais, 2022 ; Kang et al, 2022 ; Pinto-Merino et al, 2022 ). It is an aggressive and heterogeneous disease characterized by rapid proliferation and arrested differentiation of medulloblastoma in the peripheral blood, bone marrow, and other tissues ( Shapoorian, Zalpoor & Ganjalikhani-Hakemi, 2021 ; Xiang et al, 2022 ). ALL is a highly-aggressive hematological disease ( Li et al, 2022 ; Xin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [ 7 ] found that vitamin D (1,25VD3)-induced overexpression of fructose-1,6-bisphosphatase 1 (FBP1) regulates different metabolic processes in AML, which may serve as an attractive approach to block energy production in AML. Thus, targeted intervention in cancer metabolism has emerged as a potential strategy to ameliorate treatment in AML [ 8 ].…”
Section: Introductionmentioning
confidence: 99%